Study on the adsorption of nitrogen and phosphorus from biogas slurry by NaCl-modified zeolite. - Qunpeng Cheng; Hongxia Li; Yilu Xu; Song Chen; Yuhua Liao; Fang Deng; Jianfen Li (PLoS ONE, 2017)
A NaCl-modified zeolite was used to simultaneously remove nitrogen and phosphate from biogas slurry. The effect of pH, contact time and dosage of absorbants on the removal efficiency of nitrogen and phosphate were studied. The results showed that the highest removal efficiency of NH4+-N (92.13%) and PO43--P (90.3%) were achieved at pH 8. While the zeolite doses ranged from 0.5 to 5 g/100 ml, NH4+-N and PO43--P removal efficiencies ranged from 5.19% to 94.94% and 72.16% to 91.63% respectively. The adsorption isotherms of N and P removal with NaCl-modified zeolite were well described by Langmuir models, suggesting the homogeneous sorption mechanisms. While through intra-particle diffusion model to analyze the influence of contact time, it showed that the adsorption process of NH4+-N and PO43--P followed the second step of intra-particle diffusion model. The surface diffusion adsorption step was very fast which was finished in a short time.